Financing Low Carbon Transport Solutions in Developing Countries - Benitez, Daniel Alberto; Bisbey, Jyoti (World Bank, Washington, DC, 2021)
Transport is a key component to climate solution and therefore, pivotal to reach benchmarks established by the ambitious Paris Agreement. We have the technology, tools, and opportunities to advance markets, unlock investments, and scale up action. The climate action pathway – transport provides clear insights to advance and align transport with the objectives of the Paris Agreement, and is complemented by the global roadmap toward sustainable mobility. However, by most measures, action is well off-track, and greenhouse gas (GHG) emissions from transport are on the rise. At the same time, the momentum increases to drive action on transport and accelerate the transition to zero or low carbon transport modes. There are calls for decarbonizing transport and for improving the international community’s understanding of how specific investments and innovative finance solutions can create the conditions for market uptake of climate-smart solutions across transport sectors. Policy, technology, and investment are all critical in accelerating the transition toward carbon neutral transport. This document is organized as follows. Chapter 2 describes the trends on greenhouse gas emissions while Chapter 3 reviews the challenge to reduce emissions in developing countries summarizing the findings on the other TDI notes. Chapter 4 discusses the experience and trends in funding public investments and policies in the transportation sector while Chapter 5 describes the architecture of climate finance for transport decarbonization. Chapter 6 presents some innovative financial approaches and finally, Chapter 7 develops a series of recommendations for a transition to a low carbon pathway in transport.